Radical Martyrdom and Cosmic Conflict in Early Christianity. By Paul Middleton - Hammond, Carolyn (The journal of theological studies, 2010)
This book explores the motivations of certain Christians who, in the later tradition, came to be dismissed as extremists transgressing behavioural boundaries by actively seeking death at the hands of pagan ‘oppressors’—oppressors whose bewilderment at an inexplicable obduracy and determination to engineer confrontations is apparent in the historical sources. The aim is to prove that their eagerness for death, their (to be precise) active agency in their own destruction, was founded upon a secure basis in most of the writings which coalesced into the New Testament, and that it was widely admired and approved in the early centuries of Christianity.